Late Pan-African Murzuq event in the Central Hoggar: Sinistral displacement along the Ounane major shear zone (Gour Oumelalen, Algeria) shown by the magnetic fabric of the Tisselliline pluton. (December 2021) - Nouar, O.; Henry, B.; Liégeois, J.P.; Amenna, M.; Abdallah, N.; Derder, M.E.M.; Ayache, M.
Abstract: The late upper-level subcircular Tisselliline pluton (c. 572 Ma), emplaced in Hoggar along the major Pan-African Ounane shear zone, is NNW-SSE oriented. Its magnetic fabric is mainly characterized by dome-shaped magnetic foliations and subhorizontal magnetic lineations. When approaching the nearby Ounane shear zone, the lineations become associated with a prolate shape of the fabric and their direction evolves from NE-SW to NNE-SSW. This highlights a stretching underwent by the pluton during its late magmatic stage, in agreement with the shape of the pluton itself. These characteristics indicate a sinistral movement along the Ounane shear zone during the emplacement of the Tisselliline pluton. It is the opposite to the dextral movement that affected earlier the older Ounane batholith (c. 629 Ma) located on the other side of the shear zone. This sinistral movement can be related to the NE-SW compression that occurred in the Eastern Hoggar, western part of the Saharan metacraton, during the Murzukian event. Its age, given by the Tisselliline pluton age (c. 572 Ma), corresponds indeed to the initiation of this event (575-555 Ma). This shows that the Eastern Hoggar Murzukian event affected also the Central Hoggar, even if with a much lower intensity. Graphical abstract: Image 1 Highlights: The late Ediacaran Tisselliline pluton AMS highlights a stretching during magmatic stage. This stretching is related to a sinistral movement along the NNW-SSE Ounane shear zone. An opposite earlier dextral movement affected the early Ediacaran Ounane batholith. The Eastern Hoggar Murzukian event affected also the Central Hoggar.